Assessing Current Cerebral Palsy Therapy and Identifying Needs for Improvement - Tommy, Robin; Badrinarayanan, M.K.; Ravindranathan, Reshmi; George, Smitha Rosemary (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Background: Cerebral palsy (CP) is a prevalent childhood physical disability requiring long-term therapeutic interventions. Conventional rehabilitation methods face challenges maintaining engagement and providing personalized, measurable outcomes. Methods: This study assessed current CP therapy approaches through a literature review and primary data analysis. We propose an innovative digital therapeutic platform integrating gamification, virtual reality, and AI-based motion tracking. Results: Our analysis revealed limitations in traditional therapies, including lack of engagement, limited personalization, and insufficient progress tracking. The proposed technology-driven solution shows potential for enhancing motivation, customization, and measurable progress in CP rehabilitation. Conclusions: Our proposed digital platform offers promising avenues for improving rehabilitation outcomes and patient experiences by addressing key limitations in current CP therapy.